Cases and commentary on international law - Janis, Mark W. (Thomson/West, 2006)
Introduces the history and nature of international law, and examines the sources of international law—treatise, custom, general principles, jus cogens, and equity. Also covers important fields of international law: individuals and human rights; recognition and self-determination; war and peace and the United Nations; Antarctica, outer space, the law of the sea, and international environmental laws; and international conflict of laws, foreign sovereign immunity, and act of state.